2022
DOI: 10.3389/fbuil.2022.975071
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle energy analysis of residential wooden buildings versus concrete and steel buildings: A review

Abstract: Around 40% of global energy consumption can be attributed to the construction sector. Consequently, the development of the construction industry towards more sustainable solutions and technologies plays a crucial role in the future of our planet. Various tools and methods have been developed to assess the energy consumption of buildings, one of which is life cycle energy analysis (LCEA). LCEA requires the energy consumption at each stage of the life cycle of a product to be assessed, enabling the comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Figures [13][14][15][16] show the detailed relative humidity (RH) distribution in the analyzed walls. Figures 13 and 14 present the RH distribution in the winter time (end of February) both for dry and wet conditions.…”
Section: Relative Humidity Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures [13][14][15][16] show the detailed relative humidity (RH) distribution in the analyzed walls. Figures 13 and 14 present the RH distribution in the winter time (end of February) both for dry and wet conditions.…”
Section: Relative Humidity Distributionmentioning
confidence: 99%
“…One of the alternative, more environmentally sustainable substitutes for industrially produced load-bearing materials is structural timber. According to research conducted by Schenek and Amiri [15], buildings constructed with timber elements, depending on the type of technology used, exhibit a 28-47% lower carbon footprint compared to buildings constructed with traditional materials [15]. Furthermore, the dismantling processes of timber-framed buildings require approximately 50% less energy input compared to buildings made from traditional materials [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that residential timber buildings with one up to twelve stories could reduce the amount of embodied energy by 28%-47% in comparison to concrete and steel buildings (Schenk and Amiri, 2022). Additionally, another study estimated a reduction in energy consumption by 25% for a 8-story residential timber building compared to a concrete building (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Norman et al studied the energy use and greenhouse gas emissions of highly and lowpopulated buildings to demonstrate the effects of urban density [14]. Schenk et al compared the ecological impacts of wooden buildings versus concrete and steel-framed buildings utilizing the LCA [15]. Furthermore, various other types of buildings were also analyzed using LCA [16].…”
Section: Introductionmentioning
confidence: 99%